PERBANDINGAN HARGA SAHAM DAN TRADING VOLUME ACTIVITY SEBELUM DAN SETELAH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA PERIODE 2017-2018 - Michaela Nathania; Ika Yanuarti (Universitas Multimedia Nusantara, 2019)
Manufacturing companies have the main activity that is managing raw materials to become finished goods, in this process manufacturing companies have the potential to produce waste that can harm the environment and also the surrounding community. Awareness to reduce losses is done by carrying out Corporate Social Responsibility activities and disclose them in the company's annual report. This disclosure is very important for companies to improve the company's image in the public and this disclosure is useful for investors in making investment decisions because it reduces information asymmetry that can reduce uncertainty in making investment decisions. The purpose of this study is to determine the comparison of stock prices and trading volume activity (TVA) before and after the disclosure of Corporate Social Responsibility in manufacturing companies listed on the Indonesia Stock Exchange period 2017-2018. Samples were selected using purposive sampling and secondary data were analyzed using paired sample t-tests. The number of samples in this study were 46 samples of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2018 and made disclosures of Corporate Social Responsibility in 2018 and 2019. The results of this study are (1) there are no differences in stock prices before and after the disclosure of Corporate Social Responsibility 2018, (2) there are differences in trading volume activity (TVA) before and after disclosure of Corporate Social Responsibility 2018, (3) there are differences in stock prices before and after the disclosure of Corporate Social Responsibility 2019, (4) there are differences in trading volume activity (TVA) before and after the disclosure of Corporate Social Responsibility 2019. Keyword: Corporate Social Responsibility disclosure, stock price, Trading Volume Activity (TVA)